Inner‐Outer Factorization via Lur'e Equations. Issue 1 (25th October 2016) - Reis, Timo; Voigt, Matthias
Abstract: In this paper we construct inner‐outer factorizations of transfer functions governed by linear time‐invariant differential‐algebraic systems. This construction is based on the solution of certain Lur'e equations. In contrast to previous work we do not assume any condition apart from behavioral stabilizability of the underlying system realization. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)